1993
DOI: 10.1007/bf01321884
|View full text |Cite
|
Sign up to set email alerts
|

Serum osteocalcin and fracture susceptibility in elderly women

Abstract: The purpose of this investigation was to evaluate the bone turnover by using bone metabolic markers in relation to previous fracture history and independent of bone mass. Patients and controls were recruited from a population-based study of 193 women, all living in the same city and aged 60, 70, and 80 years. The bone mineral content (BMC) was measured bilaterally in the distal forearm by single-photon absorptiometry (SPA). At the same time, serum samples were obtained for biochemical analysis. Of the 193 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…However, no signi®cant association was found for total ALP, bone ALP and for procollagen type I C propeptide (PICP) [11,12]. Similar results were reported by Akesson et al [13] in a small case±control analysis, with 19% lower OC levels in 26 women who had sustained a fracture 2.8 years before the measurement compared with 26 age-matched controls. Luisitto et al [14] also reported a slight but signi®cant decrease in OC (710%) and a more pronounced decrease in total ALP (740%) in 100 women who sustained vertebral and nonvertebral fractures more than 1 year before measurement compared with 219 control subjects.…”
Section: Bone Formationsupporting
confidence: 86%
“…However, no signi®cant association was found for total ALP, bone ALP and for procollagen type I C propeptide (PICP) [11,12]. Similar results were reported by Akesson et al [13] in a small case±control analysis, with 19% lower OC levels in 26 women who had sustained a fracture 2.8 years before the measurement compared with 26 age-matched controls. Luisitto et al [14] also reported a slight but signi®cant decrease in OC (710%) and a more pronounced decrease in total ALP (740%) in 100 women who sustained vertebral and nonvertebral fractures more than 1 year before measurement compared with 219 control subjects.…”
Section: Bone Formationsupporting
confidence: 86%
“…It is now widely accepted that the accelerated rate of bone loss seen after the menopause is mainly due to an uncoupling in bone turnover and an increase in bone resorption (26,27). Studies employing specific bone markers indicate that bone turnover continues to be increased (and to be associated with bone loss) during late menopause (28)(29)(30)(31)(32)(33). In some postmenopausal women (34), but particularly in the very elderly (35)(36)(37), this increase in bone turnover is often, but not always, found to be due to vitamin D and/or calcium deficiency and secondary hyperparathyroidism.…”
Section: Menopause and Ageingmentioning
confidence: 99%
“…In retrospective population-based studies, Akesson and co-workers (28,29,43,44) have demonstrated that previous fractures were associated with abnormal bone turnover. After adjustment for age and BMD, women with fractures occurring within six years prior to the study were characterised by lower serum levels of OC and PICP, but normal rates of bone resorption.…”
Section: Bone Turnover In Osteoporosismentioning
confidence: 99%
“…Other markers, such as plasma procollagen type‐I C‐terminal (PICP) and serum bone‐specific alkaline phosphatase (B‐ALP) are also considered to be the indicators of bone formation. There seems to be a divergent response among these markers of bone formation in various diseases (17,18) . The various markers may therefore reflect different stages of the osteoblastic development and function.…”
Section: Introductionmentioning
confidence: 99%